Development and evaluation of a HOTS-based test for matrix topic: A classical test and item response theory - Muhamad Ali Misri; Saifuddin Saifuddin; Reza Oktiana Akbar; Nok Rini Kamelia (Universitas Islam Negeri (UIN) Mataram, 2021)
[English]: This research aims to develop and evaluate a higher-order thinking skill (HOTS)-based test for a matrix topic. The development was carried out in two stages; items development and validation. The first stage was to review relevant literature about HOTS, design the test items, have experts review, and try out the items. Fifty-one upper secondary school students were involved in the tryout. In the second stage, results of the tryout were validated referring to the classical test and item response theory, including items characteristics, validity and reliability, items discrimination, and difficulty levels. The validation resulted in five valid test items (r1=0,54; r2=0,88; r3=0,72; r4=0,78; r5=0,82). The developed test represents the topic, fulfills HOTS criteria, is reliable rα=0,85, can differentiate students with higher-order thinking, and has varied difficulty levels. [Bahasa]: Penelitian ini bertujuan untuk mengembangkan dan mengevaluasi soal tes berbasis keterampilan berpikir tingkat tinggi (HOTS) pada materi matriks. Pengembangan instrumen tes melalui dua tahap, yaitu pengembangan draf soal dan validasi. Pada tahap pertama, dilakukan kajian literatur yang relevan, penyusunan rencana butir soal, evaluasi butir soal yang diusulkan, dan uji coba draf butir soal. Sebanyak 51 siswa sekolah menengah dilibatkan pada tahapan uji coba. Pada tahap validasi, dilakukan analisis menggunakan teori tes klasik dan teori respon butir mencakup: karakterisasi, validitas dan reliabilitas, uji daya beda, dan tingkat kesulitan soal. Penelitian ini menghasilkan lima butir soal yang valid (r1=0,54; r2=0,88; r3=0,72; r4=0,78; r5=0,82). Tes yang dikembangkan mewakili materi matriks, memenuhi kriteria HOTS, dapat diandalkan dengan nilai reliabilitas tes sebesar rα=0,85, dapat membedakan siswa yang memiliki kemampuan berpikir tingkat tinggi, dan memiliki keragaman tingkat kesulitan.